2007
DOI: 10.1073/pnas.0709309104
|View full text |Cite
|
Sign up to set email alerts
|

Structure of sodium above 100 GPa by single-crystal x-ray diffraction

Abstract: At pressures above a megabar (100 GPa), sodium crystallizes in a number of complex crystal structures with unusually low melting temperatures, reaching as low as 300 K at 118 GPa. We have utilized this unique behavior at extreme pressures to grow a single crystal of sodium at 108 GPa, and have investigated the complex crystal structure at this pressure using high-intensity x-rays from the new Diamond synchrotron source, in combination with a pressure cell with wide angular apertures. We confirm that, at 108 GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 19 publications
4
58
0
Order By: Relevance
“…Between 2002 and 2008, a number of phase transitions of sodium at pressures up to 160 GPa were observed [42][43][44]. In 2009, in three letters to Nature in the same issue [45][46][47], it was shown that both lithium and sodium lose their metallic character under pressure.…”
Section: From Solvated Electrons To Electridesmentioning
confidence: 99%
“…Between 2002 and 2008, a number of phase transitions of sodium at pressures up to 160 GPa were observed [42][43][44]. In 2009, in three letters to Nature in the same issue [45][46][47], it was shown that both lithium and sodium lose their metallic character under pressure.…”
Section: From Solvated Electrons To Electridesmentioning
confidence: 99%
“…
Recent experiments have shown that sodium, a prototype simple metal at ambient conditions, exhibits unexpected complexity under high pressure [1][2][3][4] . One of the most puzzling phenomena in the behaviour of dense sodium is the pressureinduced drop in its melting temperature, which extends from 1000 K at ∼30 GPa to as low as room temperature at ∼120 GPa 1 .
…”
mentioning
confidence: 99%
“…From 1 bar to 200 GPa, its volume reduces by fivefold, and its Wigner-Seitz radii, r s ¼ ½3∕ð4πn e Þ 1∕3 , reduces from 3.93 to 2.33, where n e is the conduction electron density (6, 7). During such a large range of electronic densification, Na exhibits numerous surprising behaviors, including melting at 118 GPa and 300 K (3), transitions to nine high-pressure phases including some truly exotic, complex crystal structures with as many as 512 atoms per unit cell (4,8,9), and eventually to an optically transparent, insulating solid (6, 10). These structural and optical studies indirectly revealed the unique physics of FE under compression (2).…”
mentioning
confidence: 99%